Finnish pre-service primary teachers' perceptions of their preparedness to deliver sexuality education - Vuorenoja, Karla (My University, 2025)
This study investigated the perceptions current Finnish primary teacher students had of their preparedness to deliver sexuality education content in their future work as primary teachers. Sexuality education in this study is defined based on the WHO (2010) Standards for Sexuality Education in Europe. The study was conducted by utilizing the Preparedness for Sexuality Education Survey (PSES) (N = 56) and semi-structured interviews (N = 7) both constructed by the researcher. The PSES asked participants to rate their preparedness to deliver different aspects of sexuality education based on the WHO (2010) guidelines and included two open-ended questions where participants had the opportunity to elaborate their responses. The PSES was analyzed using both quantitative methods and qualitative content analysis. The interview data was analyzed using qualitative content analysis. The results suggest that while participants were aware of the importance of sexuality education and had ideas about how to implement it in their future classrooms, they were not well prepared to teach specific sexuality education content. Participants primarily found that they had not gained enough information about sexuality education during their primary teacher studies. They were concerned about their ability to deliver sexuality education safely and at a developmentally and age-appropriate level. Many participants found sexuality education important and meaningful despite being nervous and insecure about their abilities.
Keywords: sexuality education, sexuality, primary teacher education, pre-service teachers